Separator, preparing method thereof, and lithium battery comprising the separator
A separator with a crosslinkable acrylamide copolymer and fluorine-based polymer layers addresses high-temperature stability and adhesion issues, enhancing lithium battery performance.
Patent Information
- Application Number
- KR1020220024498
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-02-24
- Publication Date
- 2026-11-05
- Estimated Expiration
- 2042-02-24
AI Technical Summary
Existing separators for lithium batteries face issues with stability at high temperatures and electrode adhesion, leading to potential short circuits and reduced lifespan.
A separator comprising a porous substrate with a first coating layer of a water-based crosslinkable acrylamide copolymer and inorganic particles, and a second coating layer of a fluorine-based polymer and (meth)acrylic resin, enhancing heat resistance and electrode adhesion.
The separator improves heat resistance and electrode adhesion, resulting in enhanced lifespan characteristics for lithium batteries.
Smart Images

Figure 112022021113501-PAT00002_ABST
Abstract
Description
Technology Field
[0001] The invention relates to a separator, a method for manufacturing the same, and a lithium battery including the same. Background Technology
[0002] To meet the demands for miniaturization and high performance in various devices, the miniaturization and lightweighting of lithium batteries are becoming increasingly important. Furthermore, discharge capacity, energy density, and cycle characteristics of lithium batteries are becoming critical for applications in fields such as electric vehicles. To meet these requirements, lithium batteries with high discharge capacity per unit volume, high energy density, and excellent lifespan characteristics are required.
[0003] A separator is placed between the positive and negative electrodes in a lithium battery to prevent a short circuit. An electrode assembly comprising a positive electrode, a negative electrode, and a separator placed between the positive and negative electrodes is wound to form a jelly roll, and the jelly roll is rolled to improve the adhesion between the positive / negative electrodes and the separator in the electrode assembly.
[0004] Olefin-based polymers are widely used as separators for lithium batteries. Although olefin-based polymers have excellent flexibility, they have low strength when immersed in an electrolyte, and a short circuit in the battery may occur due to rapid thermal shrinkage at high temperatures above 100°C. To solve this, a separator with a shutdown function added using polyethylene wax on a porous olefin-based polymer substrate has been proposed, for example.
[0005] However, this separator requires improvement as its battery stability at high temperatures is insufficient. The problem to be solved
[0006] One aspect is to provide a separator that not only improves stability at high temperatures but also enhances electrode adhesion and heat resistance.
[0007] Another aspect is to provide a method for manufacturing the above-mentioned separation membrane.
[0008] Another aspect is to provide a lithium battery including the above-mentioned separator. means of solving the problem
[0009] Depending on one aspect,
[0010] A porous substrate; and a water-based crosslinkable acrylamide copolymer disposed on one or both sides of the porous substrate, and the above
[0011] A first coating layer comprising: a binder containing one or more crosslinking products selected from water-based crosslinking reactive acrylamide-based copolymers; and inorganic particles;
[0012] A fluorine-based polymer and a (meth)acrylic resin on the upper surface of the first coating layer
[0013] It includes a second coating layer,
[0014] The above-mentioned aqueous crosslinkable reactive acrylamide copolymer is provided as a separator containing two or more crosslinkable reactive groups.
[0015] Depending on the other aspect,
[0016] A step of forming a first coating layer on a porous substrate by coating a first coating composition comprising a binder comprising a water-based crosslinking reactive acrylamide copolymer; inorganic particles; and water on one or both sides of a porous substrate and drying the same; and
[0017] A method for manufacturing a separation membrane is provided, comprising the step of obtaining the separation membrane described above, including the step of forming a second coating layer by coating and drying a composition for forming a second coating layer, comprising a fluorine-based polymer, a (meth)acrylic resin, and water, on the upper portion of the first coating layer to form a second coating layer.
[0018] According to another aspect,
[0019] anode;
[0020] cathode; and
[0021] A lithium battery is provided comprising the separator disposed between the anode and the cathode. Effects of the invention
[0022] According to one aspect, it is possible to manufacture a separator capable of achieving electrode plate adhesion and improved heat resistance. By using such a separator, it is possible to manufacture a lithium battery with improved lifespan characteristics. Brief explanation of the drawing
[0023] Figure 1 is a schematic cross-sectional view of a separator according to one embodiment. FIG. 2 is a schematic diagram of a lithium battery including an electrode assembly wound in the form of a flat jelly roll according to one embodiment. FIG. 3 is a schematic diagram of a lithium battery including an electrode assembly wound in the form of a cylinder jelly roll according to one embodiment. Specific details for implementing the invention
[0024] The present inventive concept described below is subject to various modifications and may have various embodiments, and specific embodiments are illustrated in the drawings and described in detail in the detailed description. However, this is not intended to limit the present inventive concept to specific embodiments and should be understood to include all modifications, equivalents, or substitutions that fall within the scope of the description of the present inventive concept.
[0025] The terms used below are used merely to describe specific embodiments and are not intended to limit the creative concept. Singular expressions include plural expressions unless the context clearly indicates otherwise. In the following, terms such as "comprising" or "having" are intended to indicate the existence of the features, numbers, steps, actions, components, parts, components, materials, or combinations thereof described in the specification, and should be understood as not precluding the existence or addition of one or more other features, numbers, steps, actions, components, parts, components, materials, or combinations thereof. The " / " used below may be interpreted as "and" or "or" depending on the context.
[0026] In the drawings, thicknesses have been enlarged or reduced to clearly represent various layers and regions. Throughout the specification, the same reference numerals have been used for similar parts. Throughout the specification, when a part such as a layer, film, region, or plate is described as being "on" or "above" another part, this includes not only cases where it is directly above another part but also cases where there is another part in between. Throughout the specification, terms such as "first," "second," etc., may be used to describe various components, but the components should not be limited by these terms. The terms are used solely for the purpose of distinguishing one component from another.
[0027] In this specification, descriptions of any monomer(s) generally refer to a monomer that can be polymerized with another polymerizable component, such as another monomer or polymer. Unless otherwise indicated, it should be understood that once a monomer component reacts with another component to form a compound, said compound will contain residues of said component.
[0028] As used herein, the term "polymer" is intended to refer to prepolymers, oligomers, homopolymers, copolymers, and blends or mixtures thereof.
[0029] In this specification, "combination of these" may mean a mixture of components, copolymers, blends, alloys, composites, reaction products, etc.
[0030] A separator according to one embodiment, a method for manufacturing the same, and a lithium battery employing the same will be described in more detail below.
[0031] With recent technological developments in automotive batteries and increasing demand, there is a continuing need for high-capacity lithium batteries, leading to the emergence of the necessity for thin-film separators. Consequently, there is a gradually increasing demand for separators that possess high strength and heat resistance without compromising safety, while also exhibiting excellent adhesion.
[0032] The inventors have completed the invention of a separation membrane that meets the above-mentioned requirements.
[0033] A separator according to one embodiment comprises: a porous substrate; a porous substrate disposed on one or both sides of the porous substrate; a binder disposed on one or both sides of the porous substrate containing one or more selected from a water-based crosslinkable acrylamide-based copolymer and a crosslinking product of the water-based crosslinkable acrylamide-based copolymer; and an inorganic particle; and a second coating layer comprising a fluorine-based polymer and a (meth)acrylic resin on the upper portion of the first coating layer.
[0034] The first coating layer may contain, for example, a water-based crosslinkable acrylamide-based copolymer, a crosslinking product of the water-based crosslinkable acrylamide-based copolymer, or a combination thereof. In this specification, “crosslinking product of a water-based crosslinkable acrylamide-based copolymer” refers to a product obtained by the reaction of the crosslinkable reactive groups of the water-based crosslinkable acrylamide-based copolymer through the crosslinking reaction of the water-based crosslinkable acrylamide-based copolymer.
[0035] delete
[0036] The above separator has a structure in which a second coating layer, which is an adhesive layer, is laminated on one side of a first coating layer disposed on a porous substrate. The presence of this second coating layer ensures excellent adhesion of the separator to the electrode plate.
[0037] The above fluorine-based polymer is, for example, a copolymer of two or more monomers selected from the group consisting of polyvinylidene fluoride, polytetrafluoroethylene, vinylidene fluoride, hexafluoropropylene, tetrafluoroethylene, chlorotetrafluoroethylene, and perfluoromethylvinyl ether, or a combination thereof.
[0038] Examples of the above copolymer include vinylidene fluoride-hexapropylene copolymer.
[0039] (Meta)acrylic resins are, for example, polymethylmethacrylate, polybutylacrylate, (meth)acrylic copolymers, or combinations thereof.
[0040] The above (meth)acrylic copolymer may include, for example, (i) repeating units derived from (meth)acrylate, and (ii) repeating units derived from monomers containing polymerizable unsaturated groups.
[0041] The (meth)acrylate-derived repeating unit may be, for example, a conjugate base of (meth)acrylic acid, a (meth)acrylate, or a derivative thereof. The (meth)acrylate-derived repeating unit may be represented, for example, by the following Chemical Formula 1, Chemical Formula 2, Chemical Formula 3, or a combination thereof.
[0042] [Chemical Formula 1] [Chemical Formula 2] [Chemical Formula 3]
[0043]
[0044] R in the above chemical formulas 1 to 3 1 , R 2 and R 3 Each is independently hydrogen or a methyl group, and in the above chemical formula 2, M is an alkali metal.
[0045] The above alkali metal may be, for example, lithium, sodium, potassium, rubidium, or cesium.
[0046] The repeating unit derived from the above (meth)acrylate or (meth)acrylic acid may be included in an amount of 10 mol% to 70 mol%, for example 20 mol% to 60 mol%, 30 mol% to 60 mol%, or 40 mol% to 55 mol% relative to the total amount of the above (meth)acrylic copolymer.
[0047] When the repeating unit derived from the above (meth)acrylate or (meth)acrylic acid is included within the above range, the acrylic heat-resistant binder and the separator (10) containing it can exhibit excellent adhesion, heat resistance, air permeability, and oxidation resistance.
[0048] For example, the structural unit derived from the above (meth)acrylate or (meth)acrylic acid may include a repeating unit represented by Chemical Formula 2 and a structural unit represented by Chemical Formula 3, and in this case, the repeating unit represented by Chemical Formula 2 and the repeating unit represented by Chemical Formula 3 may be included in a molar ratio of 10:1 to 1:1 or 5:1 to 1:1.
[0049] Monomers containing polymerizable unsaturated groups may be one or more selected from styrene-based monomers and acid-derived monomers, or combinations thereof.
[0050] More specifically, the styrene monomer may be one or more selected from styrene, as well as methyl styrene, bromostyrene, chlorostyrene, or a combination thereof.
[0051] More specifically, the acid-derived monomer may be one or more selected from itaconic acid, acrylic acid, or combinations thereof, containing a substituent corresponding to -COOH. In this case, the (meth)acrylic resin may be cross-linked or non-cross-linked. To produce a cross-linked (meth)acrylate resin, a crosslinking agent may be further added during the polymerization step. The crosslinking agent may be one or more selected from divinylbenzene, divinylsulfone, divinyl ether, or combinations thereof.
[0052] For example, the above (meth)acrylic resin may be a styrene-ethylhexyl acrylate copolymer. In the styrene-ethylhexyl acrylate copolymer, the molar ratio of the styrene monomer to the ethylhexyl acrylate monomer is 1:9 to 9:1 or 2:8 to 8:2.
[0053] The above fluorine-based polymer and (meth)acrylic resin may be, for example, a particulate binder.
[0054] The particulate binder may have an average particle size of 100 nm to 500 nm, or 150 nm to 500 nm, 200 nm to 500 nm, 50 nm to 500 nm, 100 nm to 400 nm, 150 nm to 300 nm, or 150 nm to 250 nm. The average particle size of the particulate binder can be controlled by controlling the amount of initiator added, the amount of emulsifier added, the reaction temperature, and the stirring speed during polymer manufacturing.
[0055] With the above average particle size, for example, the particle size (D at 50% by volume ratio) in the cumulative size-distribution curve. 50 ) It may be. When the particulate binder has the above average particle size, it is easier to control the thickness of the second coating layer when forming the second coating layer, which is an adhesive layer, on the separation membrane by coating.
[0056] When the fluorine-based polymer is a particulate binder, the average particle size (d50) is 150 nm to 300 nm, for example, 250 nm, and when the acrylic resin is a particulate binder, the average particle size (d50) is 100 nm to 500 nm, for example, 500 nm.
[0057] The weight average molecular weight of the above fluorine-based polymer may be 100,000 g / mol to 1,000,000 g / mol, for example, 200,000 g / mol to 900,000 g / mol, for example, 300,000 g / mol to 800,000 g / mol, or for example, 400,000 g / mol to 800,000 g / mol. When the weight average molecular weight of the above fluorine-based polymer satisfies the above range, the separator membrane can exhibit excellent adhesion, heat resistance, air permeability, and oxidation resistance.
[0058] The weight average molecular weight of the above (meth)acrylic resin is 50,000 g / mol to 1,500,000 g / mol, 100,000 g / mol to 1,200,000 g / mol, or 200,000 g / mol to 1,000,000 g / mol, respectively. When the weight average molecular weight of the above (meth)acrylic resin satisfies the above range, the separator having a second coating layer containing the (meth)acrylic resin can exhibit excellent adhesion, heat resistance, air permeability, and oxidation resistance. The above weight average molecular weight may be the polystyrene equivalent average molecular weight measured using gel permeation chromatography.
[0059] The above (meth)acrylic resin has a glass transition temperature of 35°C to 80°C when a glass transition temperature is present. In this range, not only is the electrode adhesion excellent, but the ion conductivity is also good.
[0060] The second coating layer may further include an adhesive binder. The adhesive binder may be a polyvinyl alcohol-based binder. By including the adhesive binder in the adhesive layer, the adhesion between the separator and the electrode can be further improved.
[0061] The thickness of the first coating layer is 1 μm to 10 μm, 1 μm to 6 μm, 1 μm to 5 μm, or 1 μm to 3 μm. The thickness of the second coating layer is 0.5 μm to 5 μm, or 0.5 μm to 3 μm. Here, the thicknesses of the first coating layer and the second coating layer represent the total thickness of the first coating layer and the second coating layer, respectively. For example, if the first coating layer and the second coating layer are each coated only on one side of the porous substrate, the total thickness of the first coating layer and the second coating layer represents the cross-sectional thickness. And if the first coating layer and the second coating layer are each coated on both sides of the porous substrate, the total thickness of the first coating layer and the second coating layer represents the double-sided thickness.
[0062] When the thickness of the aforementioned second coating layer is within the above range, the adhesion to the electrode is excellent and the air permeability characteristics are excellent.
[0063] And the thickness of the first coating layer is 25% or less of the total thickness of the coating separator. The thickness of the first coating layer is, for example, 10 to 25% or 15 to 25% of the total thickness of the separator. When the thickness of the first coating layer is within the above range, excellent heat resistance at high temperatures is ensured.
[0064] The total thickness of the coating separation film having a first coating layer and a second coating layer according to one embodiment is 6 to 20 μm, or 7 to 15 μm.
[0065] The mixing weight ratio of the fluorine-based polymer and the (meth)acrylic resin in the second coating layer is 1:1 to 5:1, 1:1 to 4:1, for example, 2:1 to 4:1.
[0066] According to one embodiment, a structure may be provided in which a first coating layer and a second coating layer are sequentially disposed on one side of a porous substrate, and a second coating layer comprising a fluorine-based polymer and a (meth)acrylic resin is disposed on the other side of the porous substrate.
[0067] According to another embodiment, one or more selected from a first coating layer, a second coating layer, and a third coating layer may be disposed on another side of the porous substrate. The first coating layer and the second coating layer are as described above, and the third coating layer may contain one or more selected from inorganic particles having high heat resistance and fluorine-based polymers having excellent adhesion.
[0068] The above separator can achieve electrode plate adhesion compared to conventional separators during battery manufacturing and possesses high heat resistance. In addition, a separator manufactured using this can improve the lifespan characteristics of a lithium battery.
[0069] In the separation membrane according to one embodiment, the water-based crosslinkable reactive acrylamide copolymer contains two or more crosslinkable reactive groups. A first coating layer is formed using such a copolymer.
[0070] The above composition for forming the first coating layer comprises a water-based crosslinkable reactive acrylamide copolymer as a binder, and the acrylamide copolymer comprises two or more crosslinkable reactive groups capable of crosslinking with each other.
[0071] The composition for forming the first coating layer includes a water-based crosslinking reactive acrylamide copolymer, thereby enabling it to be used as a one-component type without a crosslinking agent, and the two or more crosslinking reactive groups can crosslink with each other through a self-condensation reaction. Through this, a separation membrane coating layer can be formed, and a separation membrane having high heat resistance characteristics compared to conventional separation membranes can be provided.
[0072] According to one embodiment, the crosslinking reactive group may include at least one first functional group selected from a carboxyl group, an amine group, and an isocyanate group; and at least one second functional group selected from a hydroxyl group, an epoxy group, and an oxazoline group; and a crosslinking reaction may occur between the first functional group and the second functional group to form a bond. For example, the crosslinking reactive group may include a carboxyl group and a hydroxyl group.
[0073] According to one embodiment, the equivalent ratio of the first functional group and the second functional group may be in the range of 30:70 to 70:30. The equivalent ratio of the first functional group and the second functional group may be, for example, in the range of 35:65 to 65:35, in the range of 40:60 to 60:40, or in the range of 45:55 to 55:45, or for example, in the range of about 50:50. In the above range, a cross-linking reaction between the first functional group and the second functional group can occur smoothly.
[0074] According to one embodiment, the acrylamide-based copolymer comprises a (N-substituted)amide-based monomer, and the (N-substituted)amide-based monomer is N,N-dialkyl(meth)acrylamide, N-ethyl(meth)acrylamide, N-isopropyl(meth)acrylamide, N,N-di(n-butyl)(meth)acrylamide, N,N-di(t-butyl)(meth)acrylamide, N,N-di(meth)acrylamide, N-ethyl(meth)acrylamide, N-isopropyl(meth)acrylamide, N-butyl(meth)acrylamide, N-methyl(meth)acrylamide, N-butyl(meth)acrylamide, N-methylol(meth)acrylamide, etc. It may include one or more selected from the group consisting of N-ethylol (meth)acrylamide, N-methylolpropane (meth)acrylamide, N-methoxymethyl (meth)acrylamide, N-methoxyethyl (meth)acrylamide, N-butoxymethyl (meth)acrylamide, and N-acryloylmorpholine.
[0075] The content of the above (N-substituted) amide monomer may be in the range of 30 to 90 mol% based on the total mole of the monomer components constituting the above acrylamide copolymer, for example, 40 to 80 mol% or 50 to 80 mol%. By using an acrylamide copolymer having the above range of (N-substituted) amide monomer, a decomposition temperature characteristic of 200°C or higher may be exhibited.
[0076] According to one embodiment, the above-mentioned aqueous crosslinking reactive acrylamide copolymer comprises a (N-substituted) amide monomer; and from carboxyl group-containing monomers, (meth)acrylate-based monomers, hydroxyl group-containing monomers, isocyanate group-containing monomers, oxazoline group-containing monomers, hydroxyl group-containing monomers, polyfunctional (meth)acrylate-based monomers, acid anhydride group-containing monomers, sulfonic acid group-containing monomers, phosphate group-containing monomers, succinimide-based monomers, maleimide-based monomers, itaconimide-based monomers, cyano-containing monomers, (meth)acrylate-aminoalkyl monomers, (meth)acrylate-alkoxyalkyl monomers, epoxy group-containing acrylic monomers, acrylic acid ester monomers having heterocyclic rings, halogen atoms, silicon atoms, etc., acryloylmorpholine, (meth)acrylate esters having alicyclic hydrocarbon groups, (meth)acrylate esters having aromatic hydrocarbon groups, and terpene compound derivative alcohols It may include one or more acrylic monomers selected from the group consisting of (meth)acrylic acid esters obtained.
[0077] Here, two or more functional groups capable of crosslinking with each other may be present in the (N-substituted) amide monomer and the acrylic monomer, or only in the acrylic monomer.
[0078] Specific examples of acrylic monomers include carboxyl group-containing monomers such as acrylic acid, (meth)acrylic acid, carboxyethyl acrylate, carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, and isocrotonic acid; A (meth)acrylate alkyl monomer having a straight-chain or branched-chain alkyl group having 1 to 20 carbon atoms in the ester portion, specifically, for example, methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate. Alkyl methacrylate monomers such as isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, iso-octadecyl (meth)acrylate, nonadecyl (meth)acrylate, myristyl (meth)acrylate, palmityl (meth)acrylate, stearyl (meth)acrylate, n-tetradecyl (meth)acrylate, etc.; Hydroxyl group-containing monomers such as (meth)acrylate 2-hydroxyethyl, (meth)acrylate 2-hydroxypropyl, (meth)acrylate 2-hydroxybutyl, (meth)acrylate 3-hydroxypropyl, (meth)acrylate 4-hydroxybutyl, (meth)acrylate 6-hydroxyhexyl, (meth)acrylate 8-hydroxyoctyl, (meth)acrylate 10-hydroxydecyl, (meth)acrylate 12-hydroxylauryl, (4-hydroxymethylcyclohexyl)methyl(meth)acrylate, etc. (meth)acrylate hydroxyalkyl, etc.Polyfunctional (meth)acrylate monomers such as hexanediol diacrylate (HDDA), tripropylene glycol diacrylate (TPGDA), ethylene glycol diacrylate (EGDA), trimethylolpropane triacrylate (TMPTA), trimethylolpropane ethoxy triacrylate (TMPEOTA), glycerin propoxylated triacrylate (GPTA), pentaerythritol tetraacrylate (PETA), or dipentaerythritol hexaacrylate (DPHA); acid anhydride-containing monomers such as maleic anhydride and itaconic anhydride; sulfonic acid-containing monomers such as 2-(meth)acrylamido-2-methylpropanesulfonic acid, (meth)acrylamidopropanesulfonic acid, sulfopropyl (meth)acrylate, and (meth)acryloyloxynaphthalenesulfonic acid; Phosphate group-containing monomers such as [2-(2-hydroxyethyl)acryloyl]phosphate; succinimide-based monomers such as N-(meth)acryloyloxymethylenesuccinimide, N-(meth)acryloyl-6-oxyhexamethylenesuccinimide, N-(meth)acryloyl-8-oxyhexamethylenesuccinimide; maleimide-based monomers such as N-cyclohexylmaleimide, N-isopropylmaleimide, N-laurylmaleimide, N-phenylmaleimide; itaconimide-based monomers such as N-methylitaconimide, N-ethylitaconimide, N-butylitaconimide, N-octylitaconimide, N-2-ethylhexylitaconimide, N-cyclohexylitaconimide, N-laurylitaconimide; Cyano-containing monomers such as acrylonitrile and (meth)acrylonitrile; (meth)acrylate aminoalkyl monomers such as (meth)acrylate aminoethyl, (meth)acrylate N,N-dimethylaminoethyl, (meth)acrylate N,N-dimethylaminoethyl, and (meth)acrylate t-butylaminoethyl; (meth)acrylate alkoxyalkyl monomers such as (meth)acrylate methoxyethyl, (meth)acrylate ethoxyethyl, (meth)acrylate propoxyethyl, (meth)acrylate butoxyethyl, and (meth)acrylate ethoxypropyl; epoxy group-containing acrylic monomers such as (meth)acrylate glycidyl;Examples include acrylic acid ester monomers having heterocyclic groups, halogen atoms, silicon atoms, etc., such as tetrahydrofurfuryl meth)acrylate, fluorine atom-containing (meth)acrylate, and silicon (meth)acrylate; acryloylmorpholine; (meth)acrylic acid esters having alicyclic hydrocarbon groups, such as cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, and dicyclofentanyl (meth)acrylate; (meth)acrylic acid esters having aromatic hydrocarbon groups, such as phenyl (meth)acrylate and phenoxyethyl (meth)acrylate; and (meth)acrylic acid esters obtained from terpene compound derivative alcohols. The acrylamide copolymer may be used by combining one or more of the acrylic monomers described above.
[0079] According to one embodiment, the molar ratio of the (N-substituted) amide monomer and the acrylic monomer may be in the range of 1:99 to 99:1. For example, the molar ratio of the (N-substituted) amide monomer and the acrylic monomer may be in the range of 20:80 to 80:20, 30:70 to 70:30, 40:60 to 60:40, or 50:50. A separator coating layer with improved heat resistance can be formed within the above range.
[0080] The weight-average molecular weight of the acrylamide-based copolymer may be 100,000 to 1,000,000 g / mol. For example, the weight-average molecular weight of the acrylamide-based copolymer may be 150,000 to 800,000 g / mol, specifically, for example, 200,000 to 700,000 g / mol, and more specifically, for example, 300,000 to 600,000 g / mol. Within the above range, a coating separator having a low shrinkage rate during high-temperature storage can be manufactured. For example, within the above range, a coating separator having a shrinkage rate characteristic of 5% or less when stored at 150°C for 1 hour can be manufactured.
[0081] The acrylamide-based copolymer may have a glass transition temperature of 150°C or higher. For example, the glass transition temperature of the acrylamide-based copolymer may be 150°C to 300°C, specifically, for example, 170°C to 280°C, and more specifically, for example, 190°C to 250°C. A heat-resistant separator coating layer can be formed within the above range.
[0082] According to one embodiment, the acrylamide-based copolymer may be a water-based crosslinking reactive polyacrylamide-acrylic acid-hydroxyethylacrylate copolymer.
[0083] According to one embodiment, the acrylamide-based copolymer may further include one or more non-acrylic monomers. By further including one or more non-acrylic monomers, the heat resistance of the copolymer and the binding strength of the separator to the porous substrate can be further improved.
[0084] The non-acrylic monomer included in the acrylamide copolymer described above may be used without particular restriction as long as it is a copolymer monomer other than the acrylic monomer described above. Examples of copolymer non-acrylic monomers may include vinyl esters, nitrogen-containing heterocyclic monomers, N-vinylcarboxylic acid amides, lactam monomers, olefin monomers, vinyl ether monomers, aromatic vinyl compounds, olefins or dienes, vinyl ethers, vinyl chloride, sulfonic acid group-containing monomers, imide group-containing monomers, isocyanate group-containing monomers, etc., and one or more of these may be selected.
[0085] Specific examples of copolymerizable non-acrylic monomers include vinyl esters such as vinyl acetate and vinyl propionate; N-vinyl-2-pyrrolidone, N-methylvinylpyrrolidone, N-vinylpyridine, N-vinylpiperidone, N-vinylpyrimidine, N-vinylpiperazine, N-vinylpyrazine, N-vinylpyrrole, N-vinylimidazole, N-vinyloxazole, N-(meth)acryloyl-2-pyrrolidone, N-(meth)acryloylpiperidine, N-(meth)acryloylpyrrolidine, N-vinylmorpholine, N-vinyl-2-piperidone, N-vinyl-3-morpholone, N-vinyl2-caprolactam, N-vinyl-1,3-oxazine-2-one, N-vinyl-3,5-morpholinedione, N-vinylpyrazole, N-vinylisooxazole, N-vinylthiazole, Examples include nitrogen-containing heterocyclic monomers such as N-vinylisothiazole and N-vinylpyridazine; N-vinylcarboxylic acid amides; lactam monomers such as N-vinylcaprolactam; olefin monomers such as isoprene, butadiene, and isobutylene; vinyl ether monomers such as methyl vinyl ether and ethyl vinyl ether; aromatic vinyl compounds such as vinyltoluene and styrene; olefins or dienes such as ethylene, butadiene, isoprene, and isobutylene; vinyl ethers such as vinylalkyl ethers; vinyl chloride; sulfonic acid group-containing monomers such as styrenesulfonic acid, allylsulfonic acid, and sodium vinylsulfonate; imide group-containing monomers such as cyclohexylmaleimide and isopropylmaleimide; and isocyanate group-containing monomers such as 2-isocyanate ethyl (meth)acrylate. These non-acrylic monomers can be used individually or in combination of two or more types.
[0086] The content of non-acrylic monomers included in the acrylamide copolymer is not particularly limited and can be used within a range that does not impair the water-based crosslinking reaction characteristics of the acrylamide copolymer and the high heat resistance characteristics of the separator. For example, non-acrylic monomers may be included in a range of 0.1 to 30 mol% based on the total molar content of the monomer components constituting the acrylamide copolymer. Within the above range, an acrylamide copolymer with improved heat resistance and substrate adhesion of the polymer can be provided.
[0087] The content of the acrylamide-based copolymer may be 10 to 100 weight% based on the total weight of the binder. For example, the content of the acrylamide-based copolymer may be 30 to 95 weight%, 50 to 90 weight%, or 60 to 80 weight% based on the total weight of the binder. Within the above range, a composition for a separator coating with improved heat resistance and substrate adhesion can be provided.
[0088] The composition for forming the first coating layer of the separation membrane may further include a water-based binder commonly used in the relevant technical field as a binder. Common water-based binders may include, for example, one or more selected from polyvinyl alcohol, polyvinyl acetate, polyacrylic acid, polyacrylic acid ester, polymethacrylic acid, polymethacrylic acid ester, poly-N-vinylcarboxylic acid amide, polyacrylonitrile, polyether, polyamide, ethylene vinyl acetate copolymer, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose, acrylonitrile styrene butadiene copolymer, and polyimide.
[0089] The inorganic particles included in the composition for forming the first coating layer of the separator can improve the stability of the battery by lowering the possibility of a short circuit occurring between the anode and the cathode through the inclusion of inorganic particles in the coating layer of the separator formed from the composition. The inorganic particles included in the composition for coating the separator may be metal oxides, metalloid oxides, or a combination thereof. Specifically, the inorganic particles may be alumina, titania, boehmite, barium sulfate, calcium carbonate, calcium phosphate, amorphous silica, crystalline glass particles, kaolin, talc, silica-alumina composite oxide particles, calcium fluoride, lithium fluoride, zeolite, molybdenum sulfide, mica, magnesium oxide, aluminum oxyhydroside (AlOOH), aluminum carbide, titanium carbide, tungsten carbide, aluminum hydroxide, boron nitride, aluminum nitride, etc. Inorganic particles are, for example, Al2O3, SiO2, TiO2, SnO2, CeO2, NiO, CaO, ZnO, MgO, ZrO2, Y2O3, It may be SrTiO3, BaTiO3, MgF2, Mg(OH)2, or a combination thereof. Considering the crystal growth properties and economic feasibility of the vinylidene fluoride-hexafluoropropylene copolymer, the inorganic particles may be alumina, titania, boehmite, barium sulfate, or a combination thereof. The inorganic particles may be spherical, plate-shaped, or fibrous, but are not limited to these forms; any form usable in the relevant technical field is acceptable. Examples of plate-shaped inorganic particles include alumina and boehmite. In this case, the reduction of the separator area at high temperatures is further suppressed, a relatively high porosity can be secured, and characteristics can be improved during penetration evaluation of lithium batteries. When the inorganic particles are plate-shaped or fibrous, the aspect ratio of the inorganic particles may be approximately 1:5 to 1:100. For example, the aspect ratio may be approximately 1:10 to 1:100. For example, the aspect ratio may be approximately 1:5 to 1:50. For example, the aspect ratio may be approximately 1:10 to 1:50. The ratio of the length of the major axis to the minor axis on the flat surface of the plate-shaped inorganic particle may be 1 to 3. For example, the ratio of the length of the major axis to the minor axis on the flat surface may be 1 to 2. For example, the ratio of the length of the major axis to the minor axis on the flat surface may be approximately 1. The aspect ratio and the ratio of the length of the major axis to the minor axis can be measured using a scanning electron microscope (SEM). Within the range of the aspect ratio and the length of the minor axis to the major axis, membrane shrinkage can be suppressed, relatively improved porosity can be secured, and the penetration characteristics of the lithium battery can be improved. When the inorganic particle is in a plate-like form, the average angle of the plate surface of the inorganic particle relative to one surface of the porous substrate is 0 to 30°. For example, the angle of the flat plane of an inorganic particle with respect to one side of a porous substrate can converge to 0 degrees. That is, one side of the porous substrate and the flat plane of the inorganic particle can be parallel.For example, if the average angle of the planar surface of the inorganic compound relative to one surface of the porous substrate is within the above range, thermal shrinkage of the porous substrate can be effectively prevented, thereby providing a separation membrane with a reduced shrinkage rate. The organic particles may be cross-linked polymers. The organic particles may be highly cross-linked polymers that do not exhibit a glass transition temperature (Tg). When using highly cross-linked polymers, heat resistance is improved, allowing for effective suppression of shrinkage of the porous substrate at high temperatures.
[0090] In the composition for forming the first coating layer of the separation membrane, the weight ratio of the total weight of the binder to the weight ratio of the inorganic particles may be 0.1:99.9 to 50:50. For example, the weight ratio of the total weight of the binder to the weight ratio of the inorganic particles may be 1:99 to 20:80, or 3:97 to 30:70. Within the above range, a composition for forming the first coating layer of the separation membrane can be provided that has excellent substrate binding strength and excellent heat resistance.
[0091] The composition for forming the first coating layer of the separator may further include organic particles. The organic particles may include, for example, styrene-based compounds and their derivatives, methyl methacrylate-based compounds and their derivatives, acrylate-based compounds and their derivatives, diallyl phthalate-based compounds and their derivatives, polyimide-based compounds and their derivatives, polyurethane-based compounds and their derivatives, copolymers thereof, or combinations thereof, but are not limited thereto; any that can be used as organic particles in the relevant technical field is acceptable. For example, the organic particles may be cross-linked polystyrene particles or cross-linked polymethyl methacrylate particles. The particles may be secondary particles formed by the aggregation of primary particles. In a separator containing secondary particles, the porosity of the coating layer is increased, thereby providing a lithium battery with excellent high-power characteristics.
[0092] The composition for forming the first coating layer may be provided in the form of a slurry by including water as a solvent capable of dispersing the components described above. The composition for forming the first coating layer may further include an organic solvent as long as it does not impair the water-based properties. The organic solvent may be an alcohol-based organic solvent. For example, the organic solvent may include one or more selected from the group consisting of methanol, ethanol, propanol, and butanol. By using an alcohol-based organic solvent, a composition for forming the first coating layer can be provided that is harmless to the body and has excellent drying properties, thereby ensuring mass production without reducing productivity. According to one embodiment, water and the organic solvent may be included in a volume ratio of 100:0 to 60:40. For example, water and the organic solvent may be included in a volume ratio of 95:5 to 80:20, and specifically, for example, in a volume ratio of 85:15 to 70:30. A composition for forming a first coating layer of a separation membrane with improved drying characteristics within the above range can be provided.
[0093] The solvent volatilizes through drying after coating the composition for forming the first coating layer of the separation membrane, so that it is not present in the coating layer of the separation membrane finally obtained.
[0094] A method for manufacturing a separation membrane according to one embodiment comprises the steps of: forming a first coating layer on a porous substrate by coating a first coating composition comprising a binder containing a water-based crosslinking reactive acrylamide copolymer; inorganic particles; and water on one or both sides of a porous substrate and drying the same; and forming a second coating layer by coating a second coating layer forming composition comprising a fluorine-based polymer, a (meth)acrylic resin, and water on the first coating layer and drying the same to obtain a separation membrane.
[0095] First, a composition for forming a first coating layer of a separation membrane is coated on one or both sides of a porous substrate while moving the porous substrate.
[0096] The method of coating a composition for forming a first coating layer of a separator on one or both sides of a moving porous substrate is not particularly limited, and one or more selected from, for example, a forward roll coating method, a reverse roll coating method, a microgravure coating method, and a direct metering coating method may be selected, but are not necessarily limited to these methods. The coating method may be, for example, a direct metering coating method.
[0097] Next, the porous substrate coated with the composition for forming the first coating layer is moved into a dryer.
[0098] A porous substrate coated with a composition for forming a first coating layer of a separator is dried by hot air inside a dryer, thereby preparing a separator with a coating layer disposed on the porous substrate. The porous substrate coated with the composition for forming a first coating layer of a separator is supplied to one side of the dryer, dried by hot air inside the dryer, and discharged through the other side of the dryer. Hot air is supplied from upper nozzles and lower nozzles that are alternately or symmetrically arranged on the upper and lower parts of the porous substrate coated with the composition for forming a first coating layer of a separator inside the dryer.
[0099] The movement speed of the porous substrate within the dryer may be the same as the coating speed. If the movement speed of the porous substrate is excessively slow, the inorganic particles included in the composition for forming the first coating layer of the separator may be mainly distributed at the interface between the coating layer and the porous substrate, thereby reducing the bonding strength between the coating layer and the porous substrate. If the movement speed of the porous substrate is excessively fast, the inorganic particles within the coating layer may be mainly distributed near the surface facing the electrode of the coating layer, thereby reducing the bonding strength between the separator and the electrode.
[0100] The hot air supply speed in the dryer may be, for example, 10 to 50 m / s, 10 to 40 m / s, 10 to 30 m / s, or 10 to 20 m / s, and the drying completion speed may exceed 15 mpm. By having a hot air supply speed and a drying completion speed within these ranges, a separation membrane with improved bending strength and peel strength can be manufactured while simultaneously improving the production speed. If the hot air supply speed is excessively slow, the inorganic particles included in the composition for forming the first coating layer of the separation membrane may be mainly distributed at the interface between the coating layer and the porous substrate, thereby reducing the bonding strength between the coating layer and the porous substrate.
[0101] The hot air drying temperature in the dryer is, for example, 30 to 80°C, 35 to 75°C, 40 to 70°C, or 45 to 65°C. By having a hot air temperature within this range, a separator with improved bending strength and peel strength can be manufactured.
[0102] The residence time of the porous substrate in the dryer is, for example, 10 to 50 seconds, 10 to 45 seconds, 10 to 40 seconds, 10 to 35 seconds, or 10 to 30 seconds. By having a residence time in the dryer within this range, a separation membrane with simultaneously improved bending strength and peel strength can be manufactured. If the residence time of the porous substrate in the dryer is excessively short, uniform phase separation may not occur. If the residence time of the porous substrate in the dryer is excessively long, shrinkage of the base film and shrinkage of the pores of the entire membrane may occur.
[0103] When hot air drying is performed inside a dryer, the non-solvent supplied into the dryer may be one or more selected from water and alcohol. The non-solvent may be, for example, water vapor. The alcohol may be, for example, methanol, ethanol, propanol, etc.
[0104] A separator according to another embodiment comprises a porous substrate; and a first coating layer disposed on one or both sides of the porous substrate, wherein the coating layer comprises a dried crosslinked product of the composition for forming the first coating layer of the separator described above.
[0105] The first coating layer comprises a binder containing a water-based crosslinkable reactive acrylamide copolymer and inorganic particles by crosslinking and drying the composition for forming the first coating layer of the separation membrane described above, and two or more crosslinkable reactive groups included in the acrylamide copolymer have a crosslinked form with each other.
[0106] The method comprises the step of forming a second coating layer by coating and drying a composition for forming a second coating layer, comprising a fluorine-based polymer, a (meth)acrylic resin, and water, on the upper surface of the first coating layer. Here, the coating and drying conditions may be carried out in the same manner as the coating and drying conditions described above for forming the first coating layer. Additionally, the composition for forming the second coating layer may further include an organic solvent, in the same manner as the composition for forming the first coating layer.
[0107] An adhesive binder may be further added to the composition for forming the second coating layer.
[0108] The thermal shrinkage rate of the separator according to one embodiment after storage at 150°C for 1 hour is 15% or less, and the thermal shrinkage rate after storage at 150°C for 10 minutes in a state containing an electrolyte is 10% or less. Here, 1M LiBF4 dissolved in propylene carbonate (PC) is used as the electrolyte. Thus, the separator according to one embodiment exhibits high heat resistance characteristics.
[0109] delete
[0110] In addition, the electrode adhesion strength of the separator according to one embodiment is 0.4 gf / mm or higher. The evaluation conditions for electrode adhesion strength are as described in Evaluation Example 4.
[0111] The above separator may have a basis weight ratio calculated by the following Formula 1 that is less than 0.6. Specifically, for example, the above separator may have a basis weight ratio of 0.55 or less, 0.5 or less, 0.48 or less, 0.47 or less, 0.46 or less, or 0.45 or less. The basis weight ratio of the above separator may be at least 0.40 or more. The above separator may have a basis weight ratio of, for example, 0.4 to 0.55, and specifically, for example, 0.45 to 0.5.
[0112] <Equation 1>
[0113] Basis weight ratio = Unit weight of coating layer / Unit weight of porous substrate
[0114] In the case of conventional coated separators, it was impossible to secure physical properties such as heat resistance at a basis weight ratio of less than 0.6, but the separator according to one embodiment can secure physical properties by using the composition for forming the first coating layer of the separator described above, thereby improving heat resistance to a desired level even at a ratio of less than 0.6.
[0115] A separation membrane comprising a first coating layer formed from the above-described composition for forming a first coating layer of a separation membrane has a unit area (1m²) 2 It can have very good physical properties with less than 0.04 black spots per unit area. The above separation membrane has a unit area (1m²) 2 The number of sunspots per ) may be 0.003 or less, 0.002 or less, or 0.001 or less.
[0116] The bending strength of an electrode assembly wound in the form of a jelly roll, which includes the separator disposed between the positive and negative electrodes, may be 460 N or more, and the peel strength may be 0.3 N / m or more. By the separator exhibiting a bending strength of 460 N or more and a peel strength of 0.3 N / m or more, the energy density and cycle characteristics of a lithium battery including the separator may be improved.
[0117] The porous substrate included in the separator may be a porous membrane containing polyolefin. Polyolefin has an excellent short-circuit prevention effect and can also improve battery stability through a shutdown effect. For example, the porous substrate may be a membrane composed of a resin such as polyolefins including polyethylene, polypropylene, polybutene, and polyvinyl chloride, or mixtures or copolymers thereof, but is not necessarily limited to these; any porous membrane that can be used in the relevant technical field is acceptable. For example, a porous membrane made of a polyolefin-based resin; a porous membrane woven from polyolefin-based fibers; a nonwoven fabric containing polyolefin; or an aggregate of insulating material particles may be used. For example, a porous membrane containing polyolefin has excellent applicability of a binder solution for manufacturing a coating layer formed on the porous substrate, and can increase the capacity per unit volume by reducing the thickness of the separator and increasing the proportion of active material in the battery.
[0118] The polyolefin used as a material for the porous substrate may be, for example, a homopolymer, copolymer, such as polyethylene or polypropylene, or a mixture thereof. The polyethylene may be low-density, medium-density, or high-density polyethylene, and high-density polyethylene may be used for mechanical strength. In addition, two or more types of polyethylene may be mixed for the purpose of imparting flexibility. The polymerization catalyst used in the preparation of polyethylene is not particularly limited, and Ziegler-Natta-based catalysts, Phillips-based catalysts, or metallocene-based catalysts may be used. For the purpose of achieving both mechanical strength and high permeability, the weight-average molecular weight of the polyethylene may be 100,000 to 12 million, for example, 200,000 to 3 million. The polypropylene may be a homopolymer, a random copolymer, or a block copolymer, and may be used alone or in a mixture of two or more. Furthermore, the polymerization catalyst is not particularly limited, and Ziegler-Natta catalysts or metallocene catalysts may be used. In addition, the stereoregularity is not particularly limited, and isotactic, syndiotactic, or atactic types may be used, but inexpensive isotactic polypropylene may be used. Furthermore, to the extent that the effects of the present invention are not compromised, additives such as polyolefins other than polyethylene or polypropylene and antioxidants may be added to the polyolefin.
[0119] The porous substrate included in the separator may include polyolefins such as polyethylene and polypropylene, for example, and a multilayer membrane of two or more layers may be used. Mixed multilayer membranes such as a polyethylene / polypropylene two-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, or a polypropylene / polyethylene / polypropylene three-layer separator may also be used, but are not limited to these; any material and composition that can be used as a porous substrate in the relevant technical field is acceptable. The porous substrate included in the separator may include a diene-based polymer prepared by polymerizing a monomer composition containing a diene-based monomer, for example. The diene-based monomer may be a conjugated diene monomer or a non-conjugated diene monomer. For example, the above-mentioned diene monomer includes one or more selected from the group consisting of 1,3-butadiene, isoprene, 2-chloro-1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 2-ethyl-1,3-butadiene, 1,3-pentadiene, chloroprene, vinylpyridine, vinylnorbornene, dicyclopentadiene, and 1,4-hexadiene, but is not necessarily limited to these, and any that can be used as a diene monomer in the relevant technical field is acceptable.
[0120] The thickness of the porous substrate included in the separator may be 1 μm to 100 μm. For example, the thickness of the porous substrate may be 1 μm to 30 μm. For example, the thickness of the porous substrate may be 5 μm to 20 μm. For example, the thickness of the porous substrate may be 5 μm to 15 μm. For example, the thickness of the porous substrate may be 5 μm to 10 μm. If the thickness of the porous substrate is less than 1 μm, it may be difficult to maintain the mechanical properties of the separator, and if the thickness of the porous substrate exceeds 100 μm, the internal resistance of the lithium battery may increase. The porosity of the porous substrate included in the separator may be 5% to 95%. If the porosity is less than 5%, the internal resistance of the lithium battery may increase, and if the porosity exceeds 95%, it may be difficult to maintain the mechanical properties of the porous substrate. The pore size of the porous substrate in the separator may be 0.01 μm to 50 μm. For example, the pore size of the porous substrate in the separator may be 0.01 μm to 20 μm. For example, the pore size of the porous substrate in the separator may be 0.01 μm to 10 μm. If the pore size of the porous substrate is less than 0.01 μm, the internal resistance of the lithium battery may increase, and if the pore size of the porous substrate exceeds 50 μm, it may be difficult to maintain the mechanical properties of the porous substrate.
[0121] The coating layer may be disposed on one or both sides of a porous substrate. The coating layer is formed from the composition for forming the first coating layer of the separation membrane described above. The coating layer may be, for example, a single-layer structure or a multi-layer structure. For example, the coating layer may be disposed only on one side of the porous substrate and not on the other side. Additionally, the coating layer may be a multi-layer structure. In the multi-layer coating layer, layers selected from organic layers, inorganic layers, and organic-inorganic layers may be arbitrarily disposed. The multi-layer structure may be a two-layer structure, a three-layer structure, or a four-layer structure, but is not necessarily limited to these structures and may be selected according to the required composite separation membrane characteristics. For example, the coating layer may be disposed on each side of the porous substrate. The coating layers disposed on each side of the porous substrate may independently be an organic layer, an inorganic layer, or an organic-inorganic layer, and at least one of these comprises the composition for forming the first coating layer of the separation membrane described above. Additionally, one or more of the coating layers disposed on each side of the porous substrate may be a multi-layer structure. In the multilayer coating layer, organic layers, inorganic layers, and layers selected from organic and inorganic layers may be arbitrarily arranged. The multilayer structure may be a 2-layer, 3-layer, or 4-layer structure, but is not necessarily limited to such a structure and may be selected according to the required composite membrane characteristics.
[0122] The coating layer included in the separator is, for example, 1 μm 2 It contains 0.3 to 0.4 pores with an average diameter of 500 nm to 1000 nm, and 1 μm 2 It contains 0.5 to 1.5 pores with an average diameter of less than 500 nm. 1 µm 2 Pores with an average diameter of 500 nm to 1000 nm are, for example, large-diameter pores, and 1 µm 2 Pores with an average diameter of less than 500 nm are, for example, small-diameter pores. By having a number of large-diameter pores and small-diameter pores within this range, the composite membrane can provide balanced air permeability.
[0123] If the number of large-diameter pores contained in the separator is less than 0.3 and the number of small-diameter pores is greater than 0.15, the permeability of the separator increases excessively. Consequently, the internal resistance of the separator impregnated with the electrolyte increases, which may degrade the cycle characteristics of the lithium battery containing the separator. If the number of large-diameter pores contained in the separator is greater than 0.4 and the number of small-diameter pores is less than 0.5, the permeability of the separator decreases excessively. Consequently, it becomes difficult for the separator to suppress the growth of lithium dendrites, etc., that occur during the charge-discharge process, increasing the likelihood of short circuits occurring in the lithium battery containing the separator. Permeability is, for example, Gurley permeability, which measures the time it takes for 100cc of air to pass through the separator according to JIS P-8117.
[0124] The surface of the coating layer included in the separator may have a morphology comprising, for example, multiple pores in the form of islands discontinuously arranged on the polymer film. The surface of the coating layer included in the separator may exhibit a morphology in which multiple pores are discontinuously arranged on the polymer film. The surface of the coating layer is basically composed of a polymer film and may have a morphology in which pores are irregularly arranged in the form of islands on the polymer film. By having such a morphology in the coating layer included in the separator, the bending strength and peel strength of the separator can be improved. Consequently, the energy density of the lithium battery including the separator can be improved, and the cycle characteristics can be improved. In contrast, the surface of the coating layer included in a conventional separator does not show a polymer film and exhibits a morphology in which multiple microparticles are interconnected to form a porous surface.
[0125] The content of inorganic particles included in the coating layer may be 99% by weight or less, or 98% by weight or less, based on the total weight of the coating layer.
[0126] The content of inorganic particles included in the coating layer formed from the composition for forming the first coating layer of the separation membrane may be 50% by weight or more, 55% by weight or more, or 60% by weight or more with respect to the total weight of the coating layer. The content of inorganic particles included in the coating layer formed from the composition for forming the first coating layer of the separation membrane may be 55% to 99% by weight, 60% to 99% by weight, or 60% to 98% by weight, or 60% to 96% by weight with respect to the total weight of the coating layer. By including particles within this range in the coating layer formed from the composition for forming the first coating layer of the separation membrane, the bending strength and peel strength of the separation membrane can be simultaneously improved.
[0127] The average particle size of the inorganic particles contained in the coating layer is 100 nm to 2 μm, 150 nm to 1.5 μm, or 200 nm to 1.0 μm. The average particle size of the inorganic particles is measured using a measuring device, for example, a laser diffraction method or a dynamic light scattering method. The average particle size of the inorganic particles is measured using, for example, a laser scattering particle size distribution meter (e.g., Horibasa LA-920), and is the value of the median particle size (D50) when 50% is accumulated from the small particle side in terms of volume conversion. By using inorganic particles having an average particle size within this range, the bonding strength between the coating layer and the porous substrate, and the bonding strength between the coating layer and the electrode, can both be improved. In addition, by using inorganic particles having an average particle size within this range, the separator containing the coating layer containing the inorganic particles can have an appropriate porosity. If the average particle size of the inorganic particles is less than 100 nm, the air permeability of the separator may decrease and the moisture content may increase.
[0128] The thickness of the coating layer is, for example, 0.5 to 4 μm, 0.5 to 2.5 μm, or 0.5 to 2 μm per side. If the thickness of the coating layer per side is excessively thick, the volume of the wound electrode assembly may increase. If the thickness of the coating layer per side is excessively thin, improved bending strength and peel strength may not be obtained. By placing the coating layer on both sides of the porous substrate, the bonding strength between the coating layer and the electrode is further improved, and as a result, volume change during charging and discharging of the lithium battery can be suppressed. For example, referring to FIG. 1, in a separator, a first coating layer (12) is placed on one side of the porous substrate (11), a second coating layer (13) is placed on top of it, and a second coating layer (13) is placed on the other side of the porous substrate (11). A first coating layer (12) may be further disposed between the porous substrate (11) and the second coating layer (13) formed on the other side of the porous substrate (11).
[0129] The porosity of the coating layer is 30% to 90%, 35% to 80%, or 40% to 70%. By having a porosity within this range, an increase in the internal resistance of the separator can be prevented, and excellent membrane strength can be provided while having excellent high-rate characteristics. The porosity of the coating layer is the volume occupied by pores in the total volume of the coating layer.
[0130] The application amount of the coating layer is, for example, 1.5 g / m² 2 Up to 4.5 g / m² 2 , 1.7g / m 2 Up to 4.5 g / m² 2 , 1.9 g / m 2 Up to 4.5 g / m² 2 , or 2.1 g / m 2 Up to 4.5 g / m² 2By having the coating layer application amount within this range, the separation membrane containing the coating layer can simultaneously provide improved heat resistance, peel strength, and flexural strength. If the coating layer application amount is excessively low, improved heat resistance, flexural strength, and peel strength may not be obtained.
[0131] The binder included in the coating layer may not have a concentration gradient in which the binder concentration increases from the interface in contact with the porous substrate of the porous layer toward the surface facing the electrode. For example, it may have a concentration gradient in which the binder concentration decreases from the interface in contact with the porous substrate of the porous layer toward the surface facing the electrode, or a concentration gradient in which there is no tendency for the concentration to change.
[0132] A lithium battery according to another embodiment includes a positive electrode, a negative electrode, and the above-described separator disposed between the positive electrode and the negative electrode.
[0133] According to one embodiment, the lithium battery comprises an electrode assembly including a positive electrode, a negative electrode, and the aforementioned separator disposed between the positive and negative electrodes, and the electrode assembly may have a form wound in the shape of a jelly roll. By including the aforementioned separator, the lithium battery can reduce black spot defects and improve quality, and since the adhesion between the electrodes (positive and negative electrodes) and the separator increases, volume change during charging and discharging of the lithium battery can be suppressed. Accordingly, the degradation of the lithium battery accompanied by volume change can be suppressed, thereby improving the lifespan characteristics of the lithium battery.
[0134] Lithium batteries can be manufactured, for example, in the following ways.
[0135] First, a negative electrode active material composition is prepared by mixing a negative electrode active material, a conductive material, a binder, and a solvent. The negative electrode active material composition is directly coated onto a metal current collector to manufacture a negative electrode plate. Alternatively, the negative electrode active material composition may be cast onto a separate support, and then a film peeled from the support is laminated onto a metal current collector to manufacture a negative electrode plate. The negative electrode is not limited to the forms listed above and may be in a form other than those listed above.
[0136] The negative electrode active material may be a non-carbon-based material. For example, the negative electrode active material may include one or more selected from the group consisting of a metal capable of forming an alloy with lithium, an alloy of a metal capable of forming an alloy with lithium, and an oxide of a metal capable of forming an alloy with lithium.
[0137] For example, the metals that can be alloyed with the lithium may be Si, Sn, Al, Ge, Pb, Bi, Sb Si-Y alloys (wherein Y is an alkali metal, alkaline earth metal, group 13–16 element, transition metal, rare earth element, or a combination thereof, and is not Si), Sn-Y alloys (wherein Y is an alkali metal, alkaline earth metal, group 13–16 element, transition metal, rare earth element, or a combination thereof, and is not Sn), etc. The element Y may be Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ge, P, As, Sb, Bi, S, Se, Te, Po, or a combination thereof.
[0138] For example, the transition metal oxide may be lithium titanium oxide, vanadium oxide, lithium vanadium oxide, etc.
[0139] For example, the above non-transfer metal oxides are SnO2, SiO2 x (0 <x<2) 등일 수 있다.
[0140] Specifically, the above negative electrode active material is Si, Sn, Pb, Ge, Al, SiOx(0 <x≤2), SnOy(0<y≤2), Li4Ti5O 12 It may be one or more selected from the group consisting of TiO2, LiTiO3, and Li2Ti3O7, but is not necessarily limited to these, and any non-carbon-based negative electrode active material used in the relevant technical field is acceptable.
[0141] In addition, a composite of the above-mentioned non-carbon-based negative electrode active material and a carbon-based material may also be used, and may additionally include a carbon-based negative electrode active material in addition to the above-mentioned non-carbon-based material.
[0142] Carbon-based materials may be crystalline carbon, amorphous carbon, or a mixture thereof. The crystalline carbon may be graphite such as non-shaped, plate-shaped, flake-shaped, spherical, or fibrous natural graphite or artificial graphite, and the amorphous carbon may be soft carbon (low-temperature calcined carbon) or hard carbon, mesophase pitch carbide, calcined coke, etc.
[0143] As conductive materials, acetylene black, ketjenblack, natural graphite, artificial graphite, carbon black, acetylene black, ketjenblack, carbon fiber, metal powders such as copper, nickel, aluminum, and silver, metal fibers, etc., may be used, and one or more types of conductive materials such as polyphenylene derivatives may be used in combination, but are not limited to these, and any material that can be used as a conductive material in the relevant technical field may be used. In addition, the aforementioned crystalline carbon-based material may be added as a conductive material.
[0144] As a binder, vinylidene fluoride / hexafluoropropylene copolymer, polyvinylidene fluoride (PVDF), polyacrylonitrile, polymethyl methacrylate, polytetrafluoroethylene and mixtures thereof, or styrene butadiene rubber-based polymer may be used, but are not limited to these, and any that can be used as a binder in the relevant technical field may be used.
[0145] As a solvent, N-methylpyrrolidone, acetone, or water may be used, but is not limited to these, and any solvent that can be used in the relevant technical field may be used.
[0146] The content of the negative electrode active material, conductive material, binder, and solvent is at a level typically used in lithium batteries. Depending on the application and composition of the lithium battery, one or more of the conductive material, binder, and solvent may be omitted.
[0147] Meanwhile, the binder used in the above cathode manufacturing may be the same as the composition for forming the first coating layer of the separator included in the coating layer of the separator.
[0148] Next, a positive active material composition is prepared by mixing a positive active material, a conductive material, a binder, and a solvent. The positive active material composition is directly coated and dried onto a metal current collector to manufacture a positive plate. Alternatively, the positive active material composition may be cast onto a separate support, and then a film peeled from the support is laminated onto a metal current collector to manufacture a positive plate.
[0149] As a positive electrode active material, it may include one or more selected from the group consisting of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, and lithium manganese oxide, but is not necessarily limited to these, and any positive electrode active material available in the relevant technical field may be used.
[0150] For example, Li a A 1-b B bD2(wherein 0.90 ≤ a ≤ 1.8, and 0 ≤ b ≤ 0.5); Li a E 1-b B b O 2-c D c (In the above formula, 0.90 ≤ a ≤ 1.8, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0.05); LiE 2-b B b O 4-c D c (In the above equation, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0.05); Li a Ni 1-b-c Co b B c D α (In the above equation, 0.90 ≤ a ≤ 1.8, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0.05, 0 < α ≤ 2); Li a Ni 1-b-c Co b B c O 2-α F α (In the above equation, 0.90 ≤ a ≤ 1.8, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0.05, 0 < α < 2); Li a Ni 1-b-c Co b B c O 2-α F2(wherein, 0.90 ≤ a ≤ 1.8, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0.05, 0 < α < 2); Li a Ni 1-b-c Mn b B c D α (In the above equation, 0.90 ≤ a ≤ 1.8, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0.05, 0 < α ≤ 2); Li a Ni 1-b-c Mn b B c O 2-α F α (In the above equation, 0.90 ≤ a ≤ 1.8, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0.05, 0 < α < 2); Lia Ni 1-b-c Mn b B c O 2-α F2(wherein, 0.90 ≤ a ≤ 1.8, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0.05, 0 < α < 2); Li a Ni b E c G d O2(wherein 0.90 ≤ a ≤ 1.8, 0 ≤ b ≤ 0.9, 0 ≤ c ≤ 0.5, 0.001 ≤ d ≤ 0.1); Li a Ni b Co c Mn d GeO2(wherein the above formula, 0.90 ≤ a ≤ 1.8, 0 ≤ b ≤ 0.9, 0 ≤ c ≤ 0.5, 0 ≤ d ≤ 0.5, 0.001 ≤ e ≤ 0.1); Li a NiG b O2(in the above equation, 0.90 ≤ a ≤ 1.8, 0.001 ≤ b ≤ 0.1); Li a CoG b O2(in the above equation, 0.90 ≤ a ≤ 1.8, 0.001 ≤ b ≤ 0.1); Li a MnG b O2(in the above equation, 0.90 ≤ a ≤ 1.8, 0.001 ≤ b ≤ 0.1); Li a Mn2G b O4(wherein 0.90 ≤ a ≤ 1.8 and 0.001 ≤ b ≤ 0.1); QO2; QS2; LiQS2; V2O5; LiV2O5; LiIO2; LiNiVO4; Li (3-f) J2(PO4)3(0 ≤ f ≤ 2); Li (3-f) Fe2(PO4)3(0 ≤ f ≤ 2); compounds represented by any one of the chemical formulas of LiFePO4 may be used:
[0151] In these chemical formulas, A is Ni, Co, Mn, or a combination thereof; B is Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, a rare earth element, or a combination thereof; D is O, F, S, P, or a combination thereof; E is Co, Mn, or a combination thereof; F is F, S, P, or a combination thereof; G is Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V, or a combination thereof; Q is Ti, Mo, Mn, or a combination thereof; I is Cr, V, Fe, Sc, Y, or a combination thereof; and J is V, Cr, Mn, Co, Ni, Cu, or a combination thereof.
[0152] Of course, a coating layer on the surface of this compound may be used, or a mixture of the compound and a compound having a coating layer may be used. This coating layer may include a coating element compound of an oxide, hydroxide, oxyhydroxide, oxycarbonate, or hydroxycarbonate of a coating element. The compounds forming this coating layer may be amorphous or crystalline. As coating elements included in the coating layer, Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr, or a mixture thereof may be used. For the coating layer formation process, any coating method may be used as long as the compound can be coated using these elements in a way that does not adversely affect the physical properties of the cathode active material (e.g., spray coating, immersion method, etc.). Since this is a matter that is well understood by those skilled in the art, a detailed explanation will be omitted.
[0153] For example, LiNiO2, LiCoO2, LiMn x O 2x (x=1, 2), LiNi 1-x Mn x O2(0 <x<1), LiNi 1-x-y Cox Mn y O2 (0≤x≤0.5, 0≤y≤0.5), LiFeO2, V2O5, TiS, MoS, etc. can be used.
[0154] In the positive electrode active material composition, the conductive material, binder, and solvent may be the same as those used in the negative electrode active material composition. Meanwhile, it is also possible to form pores inside the electrode plate by further adding a plasticizer to the positive electrode active material composition and / or the negative electrode active material composition.
[0155] The content of the cathode active material, conductive material, general binder, and solvent is at a level typically used in lithium batteries. Depending on the application and composition of the lithium battery, one or more of the above conductive material, general binder, and solvent may be omitted.
[0156] Meanwhile, the binder used in the manufacture of the anode may be the same as the composition for forming the first coating layer of the separator included in the coating layer of the separator.
[0157] Next, the aforementioned composite separator is placed between the anode and the cathode.
[0158] In an electrode assembly comprising an anode, a separator, and a cathode, the separator disposed between the anode and the cathode comprises a fully porous substrate as described above; and a coating layer disposed on both sides of the porous substrate, wherein the coating layer comprises the composition for forming the first coating layer of the separator described above.
[0159] The separator may be prepared separately and placed between the positive and negative electrodes. Alternatively, the separator may be prepared by undergoing a formation step in which an electrode assembly comprising a positive electrode, a separator, and a negative electrode is wound into a jelly roll, the jelly roll is placed in a battery case or pouch, the jelly roll is pre-charged by thermally softening it under pressure while it is placed in the battery case or pouch, the charged jelly roll is hot-rolled, the charged jelly roll is cold-rolled, and the charged jelly roll is charged and discharged under pressure.
[0160] Next, the electrolyte is prepared.
[0161] Electrolytes can be in a liquid or gel state.
[0162] For example, the electrolyte may be an organic electrolyte. Additionally, the electrolyte may be a solid. For example, it may be boron oxide, lithium oxynitride, etc., but is not limited to these; any material that can be used as a solid electrolyte in the relevant technical field may be used. The solid electrolyte may be formed on the cathode by a method such as sputtering.
[0163] For example, an organic electrolyte can be prepared. The organic electrolyte can be prepared by dissolving a lithium salt in an organic solvent.
[0164] Any organic solvent that can be used as an organic solvent in the relevant technical field may be used. Examples include propylene carbonate, ethylene carbonate, fluoroethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, methyl isopropyl carbonate, dipropyl carbonate, dibutyl carbonate, benzonitrile, acetonitrile, tetrahydrofuran, 2-methyltetrahydrofuran, γ-butyrolactone, dioxolane, 4-methyldioxolane, N,N-dimethylformamide, dimethylacetamide, dimethyl sulfoxide, dioxane, 1,2-dimethoxyethane, sulfolane, dichloroethane, chlorobenzene, nitrobenzene, diethylene glycol, dimethyl ether, or mixtures thereof.
[0165] Any lithium salt that can be used as a lithium salt in the relevant technical field may also be used. For example, LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiCF3SO3, Li(CF3SO2)2N, LiC4F9SO3, LiAlO2, LiAlCl4, LiN(C x F 2x+1 SO2)(C y F 2y+1SO2)(where x and y are natural numbers), LiCl, LiI, or mixtures thereof.
[0166] As shown in FIG. 2, the lithium battery (1) includes a positive electrode (3), a negative electrode (2), and a composite separator (4). The above-described positive electrode (3), negative electrode (2), and separator (4) are wound into an electrode assembly in the form of a flat jelly roll and then housed in a pouch (7). Subsequently, an organic electrolyte is injected into the pouch (7) and sealed to complete the lithium battery (1).
[0167] As shown in FIG. 3, the lithium battery (1) comprises a positive electrode (3), a negative electrode (2), and a separator (4). The aforementioned positive electrode (3), negative electrode (2), and separator (4) are wound into an electrode assembly in the form of a cylinder jelly roll and then housed in a battery case (5). Subsequently, an organic electrolyte is injected into the battery case (5) and sealed with a cap assembly (6) to complete the lithium battery (1). The battery case may be cylindrical, prismatic, thin-film, etc. The lithium battery may be a lithium-ion battery. The lithium battery may be a lithium-polymer battery.
[0168] Lithium batteries are suitable for electric vehicles (EVs) due to their excellent high-rate and lifespan characteristics. For example, they are suitable for hybrid vehicles such as plug-in hybrid electric vehicles (PHEVs).
[0169] The creative concept is explained in more detail through the following examples and comparative examples. However, the examples are intended to illustrate the creative concept and do not limit the scope of the creative concept to these examples alone.
[0170] (Manufacturing of separator membranes)
[0171] Example 1: Water-based crosslinking binder ((N-substituted) amide monomer 50 mol%), basis weight ratio 0.45
[0172] Coating solution 1 for forming a first coating layer was prepared by mixing 14.3 wt% of boehmite (ACTILOX 200SM, Nabaltec) with an average particle size of 0.3 μm (D50 by volume), 0.5 wt% of a crosslinking reactive acrylamide-acrylic acid-hydroxyethyl acrylic copolymer (Mw 400,000), 0.2 wt% of PVA (polyvinyl alcohol) (Daejeong Chemical, Mw 22,000), and 85 wt% of deionized water. In the crosslinking reactive acrylamide-acrylic acid-hydroxyethyl acrylic copolymer, the content of the (N-substituted) amide monomer is 50 mol% based on the total mole of the monomer components constituting the copolymer.
[0173] Separately, a coating solution 2 for forming a second coating layer was prepared by mixing 3.64 wt% of polyvinylidene fluoride, 1.2 wt% of an acrylic resin styrene-ethylhexyl acrylate copolymer (molar ratio of styrene to ethylhexyl acrylate = 8:2), 0.16 wt% of PVA (polyvinyl alcohol), and 95 wt% of deionized water (DI water).
[0174] The above coating solution 1 for forming the first coating layer was coated onto a cross-section of a polyethylene porous substrate (CZMZ, NW05535) with a thickness of 5.5 μm using a bar coating method, and then dried under conditions of a temperature of 80°C and a wind speed of 15 m / sec to form the first coating layer, thereby producing a separator having a first coating layer (thickness: 1.5 μm) with a basis weight ratio (unit weight of coating layer / unit weight of porous substrate) of 0.45.
[0175] A coating separation membrane was manufactured by coating both sides of a separation membrane having the first coating layer using the coating solution 2 for forming the second coating layer in a bar coating manner, and then drying the membrane under conditions of a temperature of 80°C and a wind speed of 15 m / sec to coat a second coating layer (adhesive layer) having a thickness of 0.5 μm on each side.
[0176] The total thickness of the second coating layer (adhesive layer) is 1 μm, and the total thickness of the finally obtained coating separation membrane is 8.0 μm. Therefore, the total thickness of the first coating layer is 19% of the total thickness of the finally obtained coating separation membrane. Here, the total thickness of the second coating layer is the sum of the thicknesses of the second coating layers formed on both sides of the porous substrate.
[0177] Example 2: Water-based crosslinking binder ((N-substituted) amide monomer 80 mol%), basis weight ratio 0.45
[0178] A coating separator was prepared by carrying out the same process as in Example 1 above, except that a crosslinking reactive acrylamide-acrylic acid-hydroxyethylacrylic copolymer was used as the crosslinking reactive copolymer, wherein the content of the (N-substituted) amide monomer was 80 mol% based on the total molar of the monomer components constituting the copolymer.
[0179] Comparative Example 1: Non-crosslinked CMC binder applied, basis weight ratio 0.5 / thickness of the second coating layer: total 1㎛ on both sides
[0180] Coating solution 1 was prepared by mixing 14.3 wt% of D50 0.3 μm boehmite (ACTILOX 200SM, Nabaltec), 0.5 wt% of carboxymethylcellulose sodium salt (CMC Medium Viscosity, Sigma-Aldrich), 0.2 wt% of PVA (polyvinyl alcohol) (Daejeong Chemical, Mw 22,000), and 85 wt% of deionized water.
[0181] Separately, a coating solution 2 for forming a second coating layer was prepared by mixing 3.64 wt% of a polyvinylidene fluoride (PVdF)-based binder, 1.2 wt% of an acrylate-based binder, 0.16 wt% of PVA (polyvinyl alcohol), and 95 wt% of deionized water.
[0182] The above coating solution 1 was coated onto a cross-section of a polyethylene porous substrate (CZMZ, NW05535) with a thickness of 5.5 μm to produce a coating separation membrane having a first coating layer with a basis weight ratio (unit weight of coating layer / unit weight of porous substrate) of 0.5.
[0183] A coating separation membrane having the first coating layer was prepared by coating both sides of the membrane using the coating solution 2 for forming the second coating layer in a bar coating manner, and then drying the membrane under conditions of a temperature of 80°C and a wind speed of 15 m / sec to coat a second coating layer (adhesive layer) having a thickness of 0.5 μm each, thereby producing a coating separation membrane having a total thickness of 1 μm of the second coating layer (adhesive layer). Here, the total thickness of the second coating layer is the sum of the thicknesses of the second coating layers formed on both sides of the porous substrate.
[0184] Comparative Example 2: Non-crosslinked CMC binder applied, basis weight ratio 0.6 / thickness of the second coating layer: total 1㎛ on both sides
[0185] Coating solution 1 was prepared by mixing 14.3 wt% of D50 0.3㎛ boehmite (ACTILOX 200SM, Nabaltec), 0.5 wt% of Carboxymethylcellulose Sodium Salt (CMC Medium Viscosity, Sigma-Aldrich), 0.2 wt% of PVA (polyvinyl alcohol) (Daejeong Chemical, Mw 22,000), and 85 wt% of DI water.
[0186] Separately, a coating solution 2 for forming a second coating layer was prepared by mixing 3.64 wt% of a polyvinylidene fluoride (PVdF)-based binder, 1.2 wt% of an acrylate-based binder, 0.16 wt% of PVA (polyvinyl alcohol), and 95 wt% of DI water.
[0187] The above coating solution 1 was coated onto a cross-section of a polyethylene porous substrate (CZMZ, NW05535) with a thickness of 5.5 μm to produce a coating separation membrane having a first coating layer with a basis weight ratio (unit weight of coating layer / unit weight of porous substrate) of 0.6.
[0188] A coating separation membrane was manufactured by coating the coating solution 2 on both sides of the separation membrane having the first coating layer using a bar coating method, and then drying the membrane under conditions of a temperature of 80°C and a wind speed of 15 m / sec to coat a second coating layer (adhesive layer) having a thickness of 0.5 μm each.
[0189] The total thickness of the second coating layer (adhesive layer) is 1 μm, and the total thickness of the finally obtained coating separation film is 8.8 μm.
[0190] Comparative Example 3: Application of non-crosslinked polyacrylamide binder, basis weight ratio 0.45 / / Thickness of the second coating layer: Total 1㎛ on both sides
[0191] Coating solution 1 for forming a first coating layer was prepared by mixing 14.3 wt% of D50 0.3 μm boehmite (ACTILOX 200SM, Nabaltec), 0.5 wt% of polyacrylamide (Mw 400,000), 0.2 wt% of PVA (polyvinyl alcohol) (Daejeong Chemical, Mw 22,000), and 85 wt% of DI water.
[0192] Separately, a coating solution 2 for forming a second coating layer was prepared by mixing 3.64 wt% of polyvinylidene fluoride, 1.2 wt% of an acrylic resin styrene-ethylhexyl acrylate copolymer (molar ratio of styrene to ethylhexyl acrylate = 8:2), 0.16 wt% of PVA (polyvinyl alcohol), and 95 wt% of deionized water (DI water).
[0193] The above coating solution 1 was coated onto a cross-section of a polyethylene porous substrate (CZMZ, NW05535) with a thickness of 5.5 μm to produce a coating separation membrane having a first coating layer with a basis weight ratio (unit weight of coating layer / unit weight of porous substrate) of 0.45.
[0194] The coating solution 2 was coated on both sides of the separator having the first coating layer using a bar coating method, and then dried under conditions of a temperature of 80°C and a wind speed of 15 m / sec to coat a second coating layer (adhesive layer) having a thickness of 0.5 μm each, thereby producing a coated separator having a total thickness of 1 μm of the second coating layer (adhesive layer). Here, the total thickness of the second coating layer is the sum of the thicknesses of the second coating layers formed on both sides of the porous substrate.
[0195] Comparative Example 4
[0196] A separation membrane was prepared in the same manner as in Example 1, except that the coating solution for forming the second coating layer was prepared by mixing 35% by weight of a divalent polyvinylidene fluoride-based binder and 95% by weight of deionized water.
[0197] Reference Example 1
[0198] A separator was prepared in the same manner as in Example 1, except that a second coating layer was not formed.
[0199] Evaluation Example 1: Evaluation of Thermal Shrinkage Rate Characteristics
[0200] The separators prepared in Example 1, Example 2, Comparative Examples 1 to 4 and Reference Example 1 were each cut to a size of approximately 10 cm in width (MD) x approximately 10 cm in length (TD), and stored under Condition 1 and Condition 2 below, respectively.
[0201] <Condition 1>
[0202] Store in a 150℃ chamber for 1 hour.
[0203] <Condition 2>
[0204] The electrolyte is supplied to the separator and stored in a chamber at 150°C for 10 minutes. The electrolyte used is 1M LiBF4 dissolved in propylene carbonate (PC).
[0205] After storing according to condition 1 or 2 above, the degree of shrinkage in the MD direction and TD direction was measured, and the thermal shrinkage rate in the MD direction and the thermal shrinkage rate in the TD direction were calculated respectively by the following Equations 2 and 3. The larger of the calculated values among the thermal shrinkage rates in the MD direction and the TD direction was calculated as the final value and listed in Table 1 below.
[0206] <Equation 2>
[0207] Thermal shrinkage rate in MD direction = (Length reduced in MD direction after evaluation of thermal shrinkage rate in electrolyte / Length of separator in MD direction before evaluation) × 100
[0208] <Equation 3>
[0209] TD-direction thermal shrinkage rate = (Length reduced in the TD direction after evaluation of thermal shrinkage rate in electrolyte / Separator length in the TD direction before evaluation) × 100
[0210] Thermal shrinkage rate (condition 1) Thermal shrinkage rate (condition 2) MD Direction (%) TD Direction (%) MD Direction (%) TD Direction (%) Example 1 2 2 8 8 Example 2 5 5 12 15 Comparative Example 1 20 15 ≥50 ≥50 Comparative Example 2 4 4 ≥30 ≥30 Comparative Example 3 ≥50 ≥50 ≥50 ≥50 Comparative Example 4 2 2 8 8 Reference Example 1 2 2 8 8
[0211] Referring to Table 1 above, the separator membranes of Examples 1 and 2 are equipped with a first coating layer and an adhesive layer using a crosslinking reactive acrylamide-based copolymer. It can be seen that the thermal shrinkage rate in both the MD direction and the TD direction of this separator membrane is significantly reduced compared to Comparative Example 1, which uses a conventional CMC that is not a crosslinking binder, and Comparative Example 3, which uses polyacrylamide that is not crosslinking reactive. Through this, it was confirmed that the high-temperature heat resistance characteristics of the separator membrane can be improved by coating the separator membrane using a crosslinking reactive acrylamide-based copolymer.
[0212] As shown in Table 1, the separator of Comparative Example 2 showed good thermal shrinkage characteristics under Condition 1, but poor thermal shrinkage characteristics under Condition 2.
[0213] Evaluation Example 2: Electrode thermal shrinkage rate in electrolyte
[0214] Anodes were placed on both sides of the separator prepared in Examples 1-2, Comparative Examples 1 to 4, and Reference Example 1, and a unit cell was prepared by bonding at approximately 80°C for 1 hour under conditions of 300 kgf / cm² and an electrolyte was provided. As the electrolyte, 1M LiBF4 dissolved in propylene carbonate (PC) was used.
[0215] The above anode was prepared by using a mixer to remove bubbles from a mixture of LiCoO2, polyvinylidene fluoride, and carbon black, a conductive material, to form a uniformly dispersed slurry for forming an anode active material layer. N-methyl 2-pyrrolidone, a solvent, was added to the mixture, and the mixing ratio of the composite anode active material, polyvinylidene fluoride, and carbon black was 98:1:1 by weight. The slurry prepared according to the above process was coated onto an aluminum foil using a doctor blade to form a thin electrode plate, which was then dried at 135°C for at least 3 hours, followed by rolling and vacuum drying processes to produce the anode.
[0216] The unit cell manufactured according to the above process was left at 150°C for 1 hour, then disassembled to measure the degree of shrinkage in the MD direction and TD direction as described in Evaluation Example 1 above. The thermal shrinkage rate in the MD direction and the thermal shrinkage rate in the TD direction were calculated according to Equations 4 and 5 below, respectively, and the larger of the calculated values between the thermal shrinkage rate in the MD direction and the thermal shrinkage rate in the TD direction was calculated as the final value and listed in Table 2 below.
[0217] <Equation 4>
[0218] Thermal shrinkage rate in MD direction = (Length reduced in MD direction after evaluation of electrode thermal shrinkage rate in electrolyte / Length of separator in MD direction before evaluation) × 100
[0219] <Equation 5>
[0220] TD-direction thermal shrinkage rate = (Length reduced in the TD direction after evaluation of electrode thermal shrinkage rate in electrolyte / Separator length in the TD direction before evaluation) × 100
[0221] Evaluation Example 3: Thermal shrinkage rate of substrate in electrolyte
[0222] A unit cell was prepared by placing aluminum foil on both sides of the separator prepared in Examples 1-2, Comparative Examples 1 to 4, and Reference Example 1, and performing adhesion at approximately 80°C for 1 hour under conditions of 300 kgf / cm². An electrolyte was provided to the unit cell. As the electrolyte, 1M LiBF₄ dissolved in propylene carbonate (PC) was used.
[0223] After leaving the above unit cell at 150°C for 1 hour, it was disassembled, and the degree of shrinkage in the MD direction and TD direction of the thermal shrinkage rate of the separator was measured according to the same method as in Evaluation Example 1. The thermal shrinkage rate in the MD direction and the thermal shrinkage rate in the TD direction were calculated according to Equations 6 and 7 below, respectively, and the larger of the calculated values between the thermal shrinkage rate in the MD direction and the thermal shrinkage rate in the TD direction was calculated as the final value and listed in Table 2 below.
[0224] <Equation 6>
[0225] Thermal shrinkage rate in MD direction = (Length reduced in MD direction after evaluation of thermal shrinkage rate of substrate in electrolyte / Length of separator in MD direction before evaluation) × 100
[0226] <Equation 7>
[0227] TD direction thermal shrinkage rate = (Length reduced in the TD direction after evaluation of substrate thermal shrinkage rate in the electrolyte / Separator length in the TD direction before evaluation) × 100
[0228] division Electrode thermal shrinkage rate in electrolyte Thermal shrinkage rate of substrate in electrolyte MD Direction (%) TD Direction (%) MD Direction (%) TD Direction (%) Example 1 2 2 9 9 Example 2 2 2 15 15 Comparative Example 1 10 10 ≥50 ≥50 Comparative Example 2 2 2 ≥50 ≥50 Comparative Example 3 15 15 ≥50 ≥50 Comparative Example 4 6 6 ≥50 ≥50 Reference Example 1 ≥50 ≥50 ≥50 ≥50
[0229] Referring to Table 2 above, it can be seen that the electrode shrinkage rate and substrate thermal shrinkage rate of the separators of Examples 1 and 2 were significantly reduced compared to the separators of Comparative Examples 1, 3, and Reference Example 1. Here, the separator of Reference Example 1 did not have a second coating layer (adhesive layer) compared to the separators of Examples 1 and 2, resulting in no electrode adhesion and poor thermal shrinkage rate in the electrolyte.
[0230] As shown in Table 2, the separators of Comparative Examples 2 and 4 showed good thermal shrinkage rates of the electrode in the electrolyte, but poor thermal shrinkage rates of the electrolyte substrate.
[0231] Evaluation Example 4: Measurement of the presence or absence of peeling of the first coating layer
[0232] Separator membranes prepared according to Examples 1 to 4, Comparative Examples 1 to 4, and Reference Example 1 were each cut into pieces approximately 5 cm in width (MD) x 5 cm in length (TD) and placed in a container. After immersing them in deionized water and shaking them, they were left for 10 minutes, after which the detachment of the first coating layer was evaluated by visual inspection. The results of this evaluation are shown in Table 3 below.
[0233] Evaluation Example 5: Electrode adhesion (wet adhesion)
[0234] A unit cell was prepared by placing an anode on one side of the separator prepared in Example 1, Example 2, Comparative Examples 1 to 4, and Reference Example 1, placing a polyethylene nonwoven fabric on the other side of the separator, and bonding it under conditions of 300 kgf / cm for 1 hour at approximately 80°C. An electrolyte was provided to the unit cell. As the electrolyte, 1M LiBF4 dissolved in propylene carbonate (PC) was used.
[0235] The above anode was prepared by using a mixer to remove bubbles from a mixture of LiCoO2, polyvinylidene fluoride, and carbon black, a conductive material, to form a uniformly dispersed slurry for forming an anode active material layer. N-methyl 2-pyrrolidone, a solvent, was added to the mixture, and the mixing ratio of the composite anode active material, polyvinylidene fluoride, and carbon black was 98:1:1 by weight. The slurry prepared according to the above process was coated onto an aluminum foil using a doctor blade to form a thin electrode plate, which was then dried at 135°C for at least 3 hours, followed by rolling and vacuum drying processes to produce the anode.
[0236] Next, the above unit cell was bonded at approximately 80°C for 1 hour under conditions of 300 kgf / cm. Afterward, it was disassembled, and the wet adhesion strength was evaluated through a peel test between the separator and the anode, and the evaluation results are listed in Table 3 below.
[0237] division Presence or absence of peeling of the primary coating layer Electrode adhesion (wet adhesion) (gf / mm) Example 1 radish 0.45 Example 2 radish 0.45 Comparative Example 1 you 0.44 Comparative Example 2 you 0.20 Comparative Example 3 you Unmeasurable Comparative Example 4 radish - Reference Example 1 radish -
[0238] As shown in Table 3, the electrode adhesion of the separators in Examples 1 and 2 was significantly improved compared to the separators in Comparative Examples 2 and 3, and no delamination of the primary coating layer occurred. In contrast, the electrode adhesion of the separator in Comparative Example 2 decreased compared to the separators in Examples 1 and 2, and the electrode adhesion of the separator in Comparative Example 3 could not be measured. Furthermore, as shown in Table 3, unlike the separators in Examples 1 to 4, the primary coating layer of the separators in Comparative Examples 1 to 3 was observed to delaminate easily.
[0239] Although one embodiment has been described above with reference to the drawings and examples, this is merely illustrative, and those skilled in the art will understand that various modifications and equivalent alternative embodiments are possible therefrom. Accordingly, the scope of protection of the present invention should be determined by the appended claims. Explanation of the symbols
[0240] 11: Porous substrate 12: First coating layer 13: Second coating layer 1: Lithium battery 2: Negative electrode 3: Anode 4: Separator 5: Battery case 6: Cap assembly 7: Pouch
Claims
Claim 1 A separator comprising: a porous substrate; a binder containing one or more selected from a water-based crosslinkable acrylamide-based copolymer and a crosslinking product of the water-based crosslinkable acrylamide-based copolymer disposed on one or both sides of the porous substrate; and an inorganic particle; a first coating layer comprising a fluorine-based polymer and a (meth)acrylic-based resin on the upper surface of the first coating layer, wherein the water-based crosslinkable acrylamide-based copolymer contains two or more crosslinkable reactive groups comprising at least one first functional group selected from a carboxyl group, an amine group, and an isocyanate group; and at least one second functional group selected from a hydroxyl group, an epoxy group, and an oxazoline group; and crosslinked by a self-condensation reaction of the first functional group and the second functional group. Claim 2 A separator according to claim 1, wherein the fluorine-based polymer is a copolymer of two or more monomers selected from the group consisting of polyvinylidene fluoride, polytetrafluoroethylene, vinylidene fluoride, hexafluoropropylene, tetrafluoroethylene, chlorotetrafluoroethylene, and perfluoromethylvinyl ether, or a combination thereof. Claim 3 A separator according to claim 1, wherein the thickness of the first coating layer is 25% or less of the total thickness of the separator. Claim 4 A separator according to claim 1, wherein the mixing weight ratio of a fluorine-based polymer and a (meth)acrylic resin in the second coating layer is 1:1 to 5:
1. Claim 5 In claim 1, the (meth)acrylic resin comprises polymethylmethacrylate, polybutylacrylate, a (meth)acrylic copolymer, or a combination thereof, and the (meth)acrylic copolymer comprises (i) repeating units derived from (meth)acrylate, and (ii) repeating units derived from monomers containing polymerizable unsaturated groups, forming a separation membrane. Claim 6 In claim 1, the second coating layer further comprises an adhesive binder, and the adhesive binder is a separation membrane comprising polyvinyl alcohol. Claim 7 delete Claim 8 A separator according to claim 1, wherein the equivalent ratio of the first functional group and the second functional group is in the range of 30:70 to 70:
30. Claim 9 In claim 1, the acrylamide-based copolymer comprises a (N-substituted)amide-based monomer, and the (N-substituted)amide-based monomer is N,N-dialkyl(meth)acrylamide, N-ethyl(meth)acrylamide, N-isopropyl(meth)acrylamide, N,N-di(n-butyl)(meth)acrylamide, N,N-di(t-butyl)(meth)acrylamide, N,N-di(meth)acrylamide, N-methylol(meth)acrylamide, etc. A separation membrane comprising one or more selected from the group consisting of N-ethylol (meth)acrylamide, N-methylolpropane (meth)acrylamide, N-methoxymethyl (meth)acrylamide, N-methoxyethyl (meth)acrylamide, N-butoxymethyl (meth)acrylamide, and N-acryloylmorpholine, wherein the content of the (N-substituted)amide monomer is in the range of 30 to 90 mol% based on the total molar of the monomer components constituting the acrylamide copolymer. Claim 10 In claim 1, the acrylamide-based copolymer is a (N-substituted) amide-based monomer; monomers containing carboxyl groups, alkyl (meth)acrylate monomers, hydroxyl group monomers, isocyanate group monomers, oxazoline group monomers, polyfunctional (meth)acrylate monomers, acid anhydride group monomers, sulfonic acid group monomers, phosphate group monomers, succinimide monomers, maleimide monomers, itaconimide monomers, cyano-containing monomers, aminoalkyl (meth)acrylate monomers, alkoxyalkyl (meth)acrylate monomers, epoxy group-containing acrylic monomers, acrylic acid ester monomers having heterocyclic rings, halogen atoms, silicon atoms, etc., acryloylmorpholine, (meth)acrylate esters having alicyclic hydrocarbon groups, (meth)acrylate esters having aromatic hydrocarbon groups, and terpene compound derivatives obtained from alcohols. A separator comprising one or more acrylic monomers selected from the group consisting of (meth)acrylic acid esters; wherein the molar ratio of the (N-substituted)amide monomer and the acrylic monomer is in the range of 1:99 to 99:
1. Claim 11 In claim 1, the acrylamide-based copolymer is a water-based crosslinking reactive polyacrylamide-acrylic acid-hydroxyethylacrylic copolymer, forming a separator. Claim 12 A separator according to claim 1, wherein the content of the acrylamide-based copolymer is 10 to 100 weight% based on the total weight of the binder. Claim 13 In claim 1, the inorganic particle is boehmite , A separation membrane comprising one or more selected from the group consisting of alumina, aluminum oxyhydroside (AlOOH), zirconia, yttria, ceria, magnesia, titania, silica, aluminum carbide, titanium carbide, tungsten carbide, boron nitride, aluminum nitride, calcium carbonate, barium sulfate, aluminum hydroxide, and magnesium hydroxide. Claim 14 In claim 1, the thermal shrinkage rate of the separator is 15% or less after storage at 150°C for 1 hour, and the thermal shrinkage rate of the separator impregnated with electrolyte is 10% or less after storage at 150°C for 1 hour. Claim 15 A separator according to claim 1, wherein the adhesion force of the separator to the electrode is 0.4 gf / mm or more. Claim 16 A method for manufacturing a separation membrane comprising the step of obtaining a separation membrane according to any one of claims 1 to 6 and claims 8 to 15, comprising: a step of forming a first coating layer on a porous substrate by coating a first coating composition comprising a binder containing a water-based crosslinking reactive acrylamide copolymer; inorganic particles; and water on one or both sides of a porous substrate and drying the same; and a step of forming a second coating layer by coating a second coating layer forming composition comprising a fluorine-based polymer, a (meth)acrylic resin, and water on the first coating layer and drying the same to form a second coating layer. Claim 17 A method for manufacturing a separation membrane according to claim 16, wherein the mixing weight ratio of the fluorine-based polymer and the (meth)acrylic resin is 1:1 to 5:
1. Claim 18 A lithium battery comprising a positive electrode; a negative electrode; and a separator according to any one of claims 1 to 6 and 8 to 15 interposed between the same.
Citation Information
Patent Citations
Composite separator for secondary battery and lithium secondary battery containing the same
KR1020190062924A
Separator for rechargeable lithium battery and rechargeable lithium battery including the same
KR1020200026595A
Separator for rechargeable lithium battery and rechargeable lithium battery including the same
KR1020200140637A
